ENHANCING CRAFT SKILLS: THE VITAL IMPACT OF TRAINING IN THE CERAMIC INDUSTRY OF LIMA, PERU - Leon, Rocio; Arteaga Dongo, Jesus; Castro Rodriguez, Diego; idme Medina, ishel; Salinas, Javier; Sulca, Lourdes (LACCEI, 2024)
This study focuses on the detailed analysis of Deco Hogar ceramics workshop, focused on highlighting the significant influence and impact of training in the ceramics industry. The process of manufacturing ceramic pieces has been delved into, from molding to final finishes, avoiding repetitions of procedures. During this analysis, a critical challenge was identified: the staff lacks specialized training. The stages of the production process have been represented through a flow diagram that details the sequence and interaction between the phases. Additionally, an Ishikawa diagram was applied to discern the fundamental causes of this deficiency. Surveys were conducted aimed at supervisors and managers of artisanal ceramic workshops to evaluate the level of importance they assigned to the previously established objectives, which were based on contributions from refereed and indexed articles, which were developed by experts in the ceramic industry. These surveys used the Likert scale, allowing us to know the degree of relevance that these objectives had in their perspectives on the effectiveness of the training in the different stages of the process. The results of the surveys were fundamental for the development of a Fuzzy Cognitive Map (DCM), a strategic tool that prioritize and evaluate the influence of the objectives set in optimizing the quality and efficiency of the workshop. This map established clear relationships and determined the relative relevance of each objective, directly linking them to the improvement of ceramic production. Focused on evidencing the crucial role of training in the ceramic industry, this study focuses on analyzing and justifying how specialized training can drive significant improvements in the efficiency and quality of ceramic production processes. The study concludes by highlighting the critical importance of specialized training to address the identified deficiencies and correct both existing defects and their impact on the productivity of the Deco Hogar workshop, contributing to the development and competitiveness of the ceramic industry.